2015
DOI: 10.1002/hrm.21678
|View full text |Cite
|
Sign up to set email alerts
|

Rater Rating-Level Bias and Accuracy in Performance Appraisals: The Impact OF Rater Personality, Performance Management Competence, and Rater Accountability

Abstract: We studied the problem of rating‐level bias and rating accuracy among retail managers of a Fortune 500 retailer. Hypotheses were tested regarding the relationship among managers’ Five‐Factor Model (FFM) personality characteristics, their competence in performance management, and their levels of bias and accuracy in appraisals made in situations differing on levels of rater accountability. Associate store managers (N = 125) rated subordinates, peers and managers under conditions of high and low rater accountabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 54 publications
2
51
0
2
Order By: Relevance
“…Research has progressed from an attempt to understand the role of rating context characteristics in isolation to understanding how they interact with each other and other determinants of performance ratings (e.g., Bernardin et al, 2016;Harari et al, 2015). A major initiative in the performance appraisal literature is to develop models that stipulate how multiple contextual characteristics interact to influence performance ratings (Ferris et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has progressed from an attempt to understand the role of rating context characteristics in isolation to understanding how they interact with each other and other determinants of performance ratings (e.g., Bernardin et al, 2016;Harari et al, 2015). A major initiative in the performance appraisal literature is to develop models that stipulate how multiple contextual characteristics interact to influence performance ratings (Ferris et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Field studies were generally not naturally occurring experiments where low and high accountability ratings were available. Indeed, only in rare cases (e.g., Bernardin, Thomason, Buckley, & Kane, 2016) do such studies make use of quasi-experimental designs (e.g., based upon archival performance rating data collected under systems with varying accountability pressures).…”
Section: Study Settingmentioning
confidence: 99%
“…Bernardin et al (2009) observed that those high on Agreeableness tended to rate the least effective performers more leniently than did other raters. People who were socially oriented, friendly, conscientious and concerned about other people's feelings tried not to make the target feel badly, even when a low rating was justified (Bernardin et al, 2009, 2016). Thus, raters who placed a high value on social interactions and sensitivity to colleagues' needs were less likely to be unduly harsh, since they would not want to risk their social ties at the workplace (Randall and Sharples, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When the assessor cares more about the performance of the organization, it will reduce the employee's performance reward, which will bring almost no leniency bias, the reduction of employee performance and the reduction of the overall salary. Bernard in study shows that the most generous assessment is a suitable human nature, and not arbitrary, the lack of a sense of responsibility and ability of performance evaluation, a highest effect of high and low humanity should evaluate the sense of responsibility that leads to the low agreeableness, high sense of responsibility that leads to the lowest leniency effect evaluation [5]. The influence of rater's emotion will affect the leniency effect of performance evaluation.…”
Section: Performance Evaluation Biasmentioning
confidence: 93%
“…This paper divides the environmental factors into social and organizational factors. Bernardin et al [5] found that when the assessor evaluation data was not officially evaluated by the management, the leniency effect reached the maximum. The empirical research of Antonioni shows that when subordinates rated their superiors, the evaluation results of the subordinates who were asked to sign were significantly higher than those of anonymous subordinates [6].…”
Section: Performance Evaluation Biasmentioning
confidence: 99%